Estimation of missing values in air pollution data using single imputation techniques - Norazian, Mohamed Noor; Shukri, Yahaya Ahmad; Azam, Ramli Nor; Mohd. Mustafa Al Bakri, Abdullah (Science Society of Thailand, 2009)
Link to publisher's homepage at http://www.scienceasia.org